Wiadomości . biuletyn NSZZ "Solidarność" Region Mazowsze, no. 47, 1982 - NSZZ "Solidarność" Reg. Mazowsze ([s.n.], 1982)
Creation and circulation: Issue no. 2=52(1983) with imprint: for internal use, issue no. 3=53(1983) with caption: newsletter for internal use